The Nlrp3 inflammasome, IL‐1β, and neutrophil recruitment are required for susceptibility to a nonhealing strain of Leishmania major in C57BL/6 mice. Issue 4 (20th January 2016) - Charmoy, Melanie; Hurrell, Benjamin P.; Romano, Audrey; Lee, Sang Hun; Ribeiro‐Gomes, Flavia; Riteau, Nicolas; Mayer‐Barber, Katrin; Tacchini‐Cottier, Fabienne; Sacks, David L.
Abstract : Leishmania major infection drives NLPR3 inflammasome dependent IL‐1β secretion in infected macrophages, leading to early and persistent neutrophil recruitment to the lesion. Apoptotic neutrophils inhibit parasite clearance by suppressing the activation of macrophages for killing and dendritic cells for promoting Th1 development. Abstract : Infection of C57BL/6 mice with most Leishmania major strains results in a healing lesion and clearance of parasites from the skin. Infection of C57BL/6 mice with the L. major Seidman strain ( Lm Sd), isolated from a patient with chronic lesions, despite eliciting a strong Th1 response, results in a nonhealing lesion, poor parasite clearance, and complete destruction of the ear dermis. We show here that in comparison to a healing strain, Lm Sd elicited early upregulation of IL‐1β mRNA and IL‐1β‐producing dermal cells and prominent neutrophil recruitment to the infected skin. Mice deficient in Nlrp3, apoptosis‐associated speck‐like protein containing a caspase recruitment domain, or caspase‐1/11, or lacking IL‐1β or IL‐1 receptor signaling, developed healing lesions and cleared Lm Sd from the infection site. Mice resistant to Lm Sd had a stronger antigen‐specific Th1 response. The possibility that IL‐1β might act through neutrophil recruitment to locally suppress immunity was supported by the healing observed in neutropenic Genista mice. Secretion of mature IL‐1β by Lm Sd‐infected macrophages in vitro was dependent on activation of the Nlrp3 inflammasome and caspase‐1. These data reveal that Nlrp3 inflammasome‐dependent IL‐1β, associated with localized neutrophil recruitment, plays a crucial role in the development of a nonhealing form of cutaneous leishmaniasis in conventionally resistant mice.